Comparison of neuropathology in Parkinson's disease subjects with and without deep brain stimulation. Issue 2 (2nd December 2016) - Pal, Gian D.; Ouyang, Bichun; Serrano, Geidy; Shill, Holly A.; Goetz, Christopher; Stebbins, Glenn; Metman, Leo Verhagen; Driver‐Dunckley, Erika; Mehta, Shyamal H.; Caviness, John N.; Sabbagh, Marwan N.; Adler, Charles H.; et al.
ABSTRACT: Background : The aim of this postmortem study was to compare, in Parkinson's disease subjects with and without bilateral subthalamic nucleus deep brain stimulation (STN‐DBS), the loss of pigmented neurons within the substantia nigra and pathological alpha‐synuclein density within the SN and other brain regions. Methods : PD subjects were identified from the Arizona Study of Aging and Neurodegenerative Disorders database (STN‐DBS = 11, non‐DBS = 156). Pigmented neuron loss scores within the substantia nigra as well as alpha‐synuclein density scores within the substantia nigra and 9 other brain regions were compared, the latter individually and in summary as the Lewy body brain load score. Results : DBS subjects had higher alpha‐synuclein density scores within the substantia nigra, olfactory bulb, and locus ceruleus, as well as higher total Lewy body brain load scores when compared with non‐DBS subjects. No differences in substantia nigra pigmented neuron loss scores were found. Conclusions : STN‐DBS subjects tend to have higher alpha‐synuclein density scores, but do not have a differential loss of substantia nigra pigmented neurons. © 2016 International Parkinson and Movement Disorder Society